2013
DOI: 10.1590/s0102-46982013000200004
|View full text |Cite
|
Sign up to set email alerts
|

A supremacia da perspectiva associacionista em práticas alfabetizadoras no 1º ano do ensino fundamental de nove anos

Abstract: O propósito deste trabalho é apresentar os resultados de uma pesquisa realizada em 2010 sobre práticas de alfabetização em uma turma do 1º ano da rede municipal de Pelotas-RS. Os procedimentos metodológicos foram realizados através de análise documental (LE GOFF, 1992) e da abordagem etnográfica (COHN, 2005; GEERTZ, 2008), considerando principalmente os estudos sobre alfabetização desenvolvidos por Soares (2001a, 2004a), Kramer (2006) e Peres (2009). Os dados foram coletados através da análise dos cadernos das… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Thus, the research period comprised the months of August to September 2018 and February to July 2019. During this period, 3-We believe that the meaning of the experience of the child body, in the transition that one school segment to the other provides, is what characterizes the novelty of this study, among so many others already consolidated in this theme, such as: Neves (2010); Nogueira (2011); Marcondes (2012); Fernandes (2014);and Raniro (2016).…”
mentioning
confidence: 85%
“…Thus, the research period comprised the months of August to September 2018 and February to July 2019. During this period, 3-We believe that the meaning of the experience of the child body, in the transition that one school segment to the other provides, is what characterizes the novelty of this study, among so many others already consolidated in this theme, such as: Neves (2010); Nogueira (2011); Marcondes (2012); Fernandes (2014);and Raniro (2016).…”
mentioning
confidence: 85%
“…Research has shown that some Brazilian kindergarten and first-grade teachers viewed the act of reading to students as "wasting time." Of greater importance to them were activities such as copying texts from the blackboard, completing textbook exercises, and memorizing lessons (Nogueira & Peres, 2013;Peres, 2009).…”
Section: Brazil's Education Systemmentioning
confidence: 99%